Current building strategies in Greenland - Møller Eva B.; Lading Tove (E3S Web of Conferences, 2020)
Most buildings in Greenland are built within the last 70 years. Within this relatively short period, the building styles have often changed; from small wooden houses in the 50ties to also encompass more industrialised buildings in the 70ties, and later more diverse technics. This paper describes the major tendencies in building construction of today. Apart from an extreme climate, one of the challenges in Greenland is the lack of building materials; almost everything has to be imported. Greenland is an island-operated community, with no interlinking road grid between towns and settlements. Therefore, everything must be transported by ship or plane. Furthermore, severe mould growth is a big problem. Consequently, three building strategies are currently prevailing. 1) In-situ concrete gables and partitioning walls, and facades with wooden studs. 2) Focus on non-organic material and therefore concrete structures with exterior insulation. 3) Strategies focussing on the process e.g. mainly using prefabricated elements. The paper describes the pro and cons for the different strategies seen in a Greenlandic context. The harsh climate makes Greenland a good test site for assessing new building designs. Furthermore, assessment of sustainability might be very different in Greenland from countries where resources and transportation is very different.